Corpo, práticas corporais e legitimidade da educação física nos anos finais do ensino fundamental da escola de aplicação da Universidade Federal do Pará - FREITAS, Tayná Keicy da Silva (2023)
This research sought to investigate and discuss the body, bodily practices and the legitimacy of Physical Education in Elementary School in Physical Education classes at the School of Application of the Federal University of Pará, from the perspectives of the institution's teachers. It aims to understand how Elementary School teachers (final years) of the School of Application of the Federal University of Pará work in school culture in search of recognition of the discipline of Physical Education and a new place for the body in their schooling practices. . As a method of data analysis, we used documental research and content analysis to interpret data from semi-structured interviews and teaching plans. We point out that for the teachers of the School of Application, the body is part of the total human being, and cannot be separated in their classes. Thus, there are indications of a subject body in Physical Education classes at the School of Application, which is a way to innovate and legitimize the discipline. The study indicates that there is a more critical thinking on the part of teachers and managers in relation to the discipline of Physical Education in the school field, beyond the fragmented look of it as an area of sports practices that end up delegitimizing its importance.